Peranan Epistemologi Dalam Pengembangan Pendidikan Islam - Manar, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of making this journal is to find out the role of epistemology in the development of Islamic education because epistemology is a theory of knowledge that is the basis for the development of Islamic education. This journal uses the library research method. Library study is a data collection technique by conducting a review study of books, literature, notes and reports that are related to the problem being solved. The nature of this type of writing is open exploration and is carried out in an effort to find what is relevant to the problem topic. So, this writing utilizes data that comes from written sources, the data comes from scientific works published in book form. Meanwhile, the quality of findings from library research depends on the ability, experience and sensitivity of the author in reviewing existing information. This type of library research discusses descriptive research and tends to use descriptive analysis. In this case the author starts from the data, uses existing theory as explanatory material, and ends with an explanation in the form of theory, So, this writing is descriptive, emphasizes process and meaning, and aims to produce theoretical data. Education turns out to have a very important role, even the most important in developing Islamic civilization and achieving the glory of Muslims. Judging from its formal object, education is indeed a means for human abilities to be discussed and developed. In matters of progress of civilization and the Islamic ummah, human ability must be the main concern, because it is the determining factor. This means that the study of education is directly related to the development of human resources, which have recently been believed to be more capable of accelerating the progress of civilization than natural resources. Epistemology is a process-based approach, so epistemology gives rise to very complex logical and problematic consequences, namely: Islamic education is often impressed as traditional and conservative education, Islamic education seems less concerned with the problem of how to change cognitive religious knowledge into something " meaning and value" which need to be internalized within a person through various means, media and forums. Religious teaching methodology runs conventionally and traditionally. Religious teaching relies on a static, indoctrinative-doctrinaire form of methodology.